2003
DOI: 10.1111/j.1469-8986.2003.00142.x
|View full text |Cite
|
Sign up to set email alerts
|

Recognition of affective prosody: Continuous wavelet measures of event‐related brain potentials to emotional exclamations

Abstract: The affective state of a speaker can be identified from the prosody of his or her speech. Voice quality is the most important prosodic cue for emotion recognition from short verbal utterances and nonverbal exclamations, the latter conveying pure emotion, void of all semantic meaning. We adopted two context violation paradigms-oddball and priming-to study the event-related brain potentials (ERP) reflecting this recognition process. We found a negative wave, the N300, in the ERPs to contextually incongruous excl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
106
1
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 140 publications
(115 citation statements)
references
References 60 publications
6
106
1
2
Order By: Relevance
“…This result parallels several previous studies [3,45], which investigated affective priming effects using auditory stimuli (e.g., emotional prosody, auditory emotion name) as primes and using written emotional words or auditory exclamations as targets. Schirmer et al [45] found that incongruous words elicited a larger N400 than congruous words and suggested that emotional prosody context operates in a similar way as semantic sentence context.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…This result parallels several previous studies [3,45], which investigated affective priming effects using auditory stimuli (e.g., emotional prosody, auditory emotion name) as primes and using written emotional words or auditory exclamations as targets. Schirmer et al [45] found that incongruous words elicited a larger N400 than congruous words and suggested that emotional prosody context operates in a similar way as semantic sentence context.…”
Section: Discussionsupporting
confidence: 74%
“…There was a larger N400 to words that were spoken with incongruous compared to congruous prosody. Similar findings have also been reported by Bostanov and Kotchoubey [3] using auditory emotion name -exclamation pairs. They found a negative wave, the N300, in ERPs to contextually incongruous exclamations, and interpreted this component as analogous to the well-known N400 response to semantically inappropriate words.…”
supporting
confidence: 78%
“…Hearing emotional exclamations of other persons presumes processing of affective prosody, which expresses the emotions of the speaker (Bostanov & Kotchoubey, 2004;Scherer, 1986). Whereas linguistic prosody, which specifies the semantic and syntactic structure of a sentence, largely involves the rhythm, rate, and pitch, affective prosody, conveying the information of the emotional state of the speaker, mostly relies on voice quality defined on rather brief (tens to hundreds of milliseconds) intervals (Scherer, 1986).…”
mentioning
confidence: 99%
“…Ainsi, l'élaboration de liens structurels entre les éléments d'une séquence (mots, notes, visages, objets) ferait appel à des ressources similaires à ces différents domaines. Certains travaux ont également rapporté l'occurrence d'une composante N300 dans d'autres contextes que le contexte imagé, en particulier lors de la présentation d'exclamations discordantes dans un paradigme d'amorçage mot-son (plaisir-[rage]) [32] ou encore après le calcul de multiplication mathématique en comparaison avec une situation d'addition/soustraction [33]. En résumé, bien que les études portant sur la composante N300 soient encore peu nombreuses par rapport aux travaux consacrés à la N400, il est maintenant bien établi que la N300 est une composante distincte de la N400 engendrée par des sources corticales différentes.…”
Section: Composante N300unclassified